Effects of statute 100 in the field of study and professinal practice of health professionals. The dental practice and its case - Jaramillo-D., Gonzalo H.; Gómez-B., Gloria Marcela (Revista Facultad de Odontología Universidad de Antioquia, 2009)
This essay approaches the effects that the reform to the General System of Social Security or Satatute 100 of 1993 have brought on to the practicing dentist in its political dimensions, educational processes and professional practice, and how these dimensions are being transformed as a product of an excluding and merchantilist system, affecting in a specific manner the work environment, the professional practice, the social profile obtained by the dentist and generating along the way a deep crisis in the educational models that project it socially and politically.